WORD GROUPING ACTIVITY TO IMPROVE STUDENTS' VOCABULARY MASTERY: A CLASSROOM ACTION RESEARCH - PURNA WIRATNO; HAJJAH ZULIANTI; OSHA NABILA (JETA (Journal of English Teaching and Applied Linguistic), 2023)
This research aimed to improve students' vocabulary mastery through Word Grouping Activity. The subject of this research was the 11th IPA 6 At SMA Negeri 16 Bandar Lampung. It consisted of 30 students', this research used Classroom  Action  Research (CAR) which was consisted of 2 cycle in collecting the data, the writer used test and non-test. The test used in this research were formative and summative test. Meanwhile in non-test, the writer used observation sheet and field note. In analyzing the data, the writer used quantitative and qualitative method. Refer to the result of the test, it showed that there were 13 students who got score > 75 with the presentage 70.67 % in first cycle. Meanwhile, there were 22 students who got score > 75 with the presentage 78.67 % in the second cycle. In the other hand, the mean score of the students' learning activity in the first cycle was 6.4 and in the second cycle was 7.29.It showed that were was an Increased in the students' learning activity. Based on the result of the research, the Word Grouping Activity can improve students' vocabulary mastery through at the eleventh grade at SMA Negeri 16 Bandar Lampung.